Respuesta :

Answer:

[tex]\frac{dy}{dx}=\frac{4y-2x}{y-4x}[/tex]

Step-by-step explanation:

[tex]\frac{d}{dx}(2x^2)=4x[/tex]

[tex]\frac{d}{dx}(y^2)=2y\frac{dy}{dx}[/tex]

[tex]\frac{d}{dx}(8xy)[/tex]

[tex]=8\frac{d}{dx}(xy)[/tex]

[tex]=8(\frac{d}{dx}(x)y+x\frac{d}{dx}(y))[/tex]

[tex]=8[1y+x\frac{dy}{dx}][/tex]

[tex]=8y+8x\frac{dy}{dx}[/tex]

Let's put it altogether now:

[tex]2x^2+y^2=8xy[/tex]

Differentiating both sides gives:

[tex]4x+2y\frac{dy}{dx}=8y+8x\frac{dy}{dx}[/tex]

We are solving for dy/dx so we need to gather those terms on one side and the terms without on the opposing side:

I'm going to first subtract 4x on both sides:

[tex]2y\frac{dy}{dx}=8y-4x+8x\frac{dy}{dx}[/tex]

I'm not going to subtract 8xdy/dx on both sides:

[tex]2y\frac{dy}{dx}-8x\frac{dy}{dx}=8y-4x[/tex]

It is time to factor the dy/dx out of the two terms on the left:

[tex]\frac{dy}{dx}(2y-8x)=8y-4x[/tex]

Divide both sides by (2y-8x):

[tex]\frac{dy}{dx}=\frac{8y-4x}{2y-8x}[/tex]

Reduce right hand side fraction:

[tex]\frac{dy}{dx}=\frac{4y-2x}{y-4x}[/tex]

Answer:

[tex]\frac{8y-4x}{2y-8x}[/tex]

Step-by-step explanation:

Differentiate implicitly with respect to x

noting that

[tex]\frac{d}{dx}[/tex] (y² ) = 2y[tex]\frac{dy}{dx}[/tex]

Differentiate 8xy using the product rule

Given

2x² + y² = 8xy, then

4x + 2y[tex]\frac{dy}{dx}[/tex] = 8x[tex]\frac{dy}{dx}[/tex] + 8y

Collect terms in [tex]\frac{dy}{dx}[/tex]

2y[tex]\frac{dy}{dx}[/tex] - 8x[tex]\frac{dy}{dx}[/tex] = 8y - 4x

[tex]\frac{dy}{dx}[/tex] (2y - 8x) = 8y - 4x

[tex]\frac{dy}{dx}[/tex] = [tex]\frac{8y-4x}{2y-8x}[/tex]